Revitalisasi UMK melalui Edukasi Penerapan Manajemen Berbasis Sustainable Oriented Innovation dan Pemasaran Berbasis Online: Revitalization of MSE through Education on the Implementation of Management Based on Sustainable Oriented Innovation and Online-Based Marketing - Rusgianto, Sulistya; Fathurrohman, Muhammad Said; Bayuny, Ahmad Fadlur Rahman; Fauzi, R. Mohammad Qudsi; Robbani, Ridho; Kanasibah, Auvi Diyanati; Wedari, Dinda Tamara (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Pesanggaran Village is an area that is very rich in natural potential. Located in the Pesanggaran sub-district, Banyuwangi Regency, this village has great agriculture, animal husbandry, and fisheries potential. However, in this village, community groups need help with animal husbandry. The main problem in this community group is a need for more understanding of sustainable management and, secondly, a need for more understanding of digital marketing. Using a case study method on the Silugonggo Community group, in this community service, the solution discussed in the paper is management based on sustainable-oriented innovation and online marketing. The results of this community service are that the Silugonggo Community group can increase their insight regarding management based on sustainable-oriented innovation and market their products online, primarily through e-commerce platforms.